The Relationship Between Work Shifts and Changes in Vital Signs of Health Workers: A Quantitative Study in Amalia Medika Pelalawan Riau Hospital - Pertiwi, Shanti Asih; Wahyudi, Bayu; Widjaja, Yani Restiani (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to determine the effect of work shifts on changes in vital signs of health workers at Amalia Medika Pelalawan Riau Hospital, including blood pressure, pulse frequency, body temperature, respiratory frequency, and oxygen saturation. The method used is verifiable quantitative research with a comparative design. The research population is all health workers who work with a shift system at Amalia Medika Pelalawan Riau Hospital as many as 26 people, who are used as samples with total sampling techniques. Data collection was carried out through observation, questionnaires, and documentation, then analyzed with the Chi-Square test to determine whether or not there was a correlation of work shifts on changes in vital signs. The results of the study showed that work shifts did not have a significant effect on changes in vital signs of health workers. The Chi-Square test on blood pressure produces an Asymp value. Sig 0.444, at a pulse frequency of 0.428, at a body temperature of 0.744, at a respiratory rate of 0.541, and at oxygen saturation of 0.838, are all greater than 0.05. These findings indicate that the difference in morning, noon, and night shifts did not cause significant changes in the vital signs of health workers at Amalia Medika Pelalawan Riau Hospital. This condition shows that the shift management implemented by hospitals relatively does not cause measurable physiological impairment in health workers, although other factors such as subjective fatigue or circadian rhythm disturbances still require attention.